Physiology and production of 'Niagara Rosada' grapevine in vertical shoot positioning and in Y-shaped training systems - Sanchez-Rodriguez, Luz Angela; Dias, Carlos Tadeu; Spósito, Marcel Bellato (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to characterize the physiological and productive variables of 'Niagara Rosada' vine (Vitis labrusca) trained in vertical shoot positioning (VSP) and in Y-shaped systems, in the first two years of production. In the 2014 and 2015 growing seasons, the following parameters were evaluated: leaf area index, photosynthesis, transpiration, stomatal conductance, leaf surface area, production variables, and fruit quality. In the first year of production, there were differences between the training systems for the ecophysiological variables affected by the leaf surface area of the canopies. In the second year of production, there were no differences between the ecophysiological variables. The number of clusters per leaf surface area, cluster mass, number of berries per cluster, and production per plant showed no differences between the training systems. Vines in the first and second years of production showed no differences between the two training systems for the relationships between leaf surface area and production; however, yield was higher in the VSP system because of the greater number of plants per hectare. Fruit produced in the Y-shaped system showed a greater amount of pigments, such as anthocyanins and flavonols, than those in the VSP system, with the same amount of total soluble solids.